Pharmacogenetics of treatments for inflammatory bowel disease. (2nd December 2018) - Lucafò, Marianna; Franca, Raffaella; Selvestrel, Davide; Curci, Debora; Pugnetti, Letizia; Decorti, Giuliana; Stocco, Gabriele
ABSTRACT: Introduction : Inflammatory bowel disease is a chronic inflammation of the gut whose pathogenesis is still unclear. Although no curative therapy is currently available, a number of drugs are used in induction and maintenance therapy; however, for most of these drugs, a high inter-individual variability in response is observed. Among the factors of this variability, genetics plays an important role. Areas covered : This review summarizes the results of pharmacogenetic studies, considering the most important drugs used and in particular aminosalycilates, glucocorticoids, thiopurines, monoclonal antibodies and thalidomide. Most studies used a candidate gene approach, even if significant breakthroughs have been obtained recently from applying genome-wide studies. When available, also investigations considering epigenetics and pharmacogenetic dosing guidelines have been included. Expert opinion : Only for thiopurines, genetic markers identified as predictors of efficacy or adverse events have allowed the development of dosing guidelines. For the other drugs, encouraging results are available and great expectations rely on the study of epigenetics and integration with pharmacokinetic information, especially useful for biologics. However, to improve therapy of IBD patients with these drugs, for implementation in the clinics of pharmacogenetics, informatic clinical decision support systems and training about pharmacogenetics of health providers are needed.